Quantitative Assessment of Posterior Maxillary Arch for Orthodontic Miniscrew Insertion Using Cone Beam Computed Tomography: A Cross-Sectional Analysis - Solmaz Valizadeh; A. Hamid Zafarmand; Sara Hassan Yazdi; Mitra Ghazizadeh Ahsaie (International Journal of Dentistry)
Background and Aim. The aim of this study is to assess the cortical bone thickness and interradicular distance between posterior maxillary teeth using cone beam computed tomography (CBCT). Methods and Materials. Cone beam computed tomography records of 35 patients (70 quadrants) from maxilla were evaluated. The images were analyzed using the NNT viewer software (version 23). The measurements were made on axial sections at 2, 4, 6, and 8 mm from CEJ. The optimal sites were defined in terms of mesiodistal palatal or buccal interradicular distance, alveolar cortical bone thickness, and palatal or buccal safe depth of the bone for miniscrew insertion. Descriptive statistics, paired t-test, and repeated measure ANOVA were used to analyze the data. Results. The mean buccal interradicular distance was the lowest between first and second molar (2.44 mm) and the highest between first and second premolar (3.28 mm). The mean palatal interradicular distance was the lowest between first and second premolar (3.64 mm) and the highest between second premolar and first molar (5.30 mm). The mean buccal safe depth was the lowest between canine and first premolar (1.96 mm) and the highest between first and second molar (2.61 mm). The mean palatal safe depth was the lowest between second premolar and first molar (3.35 mm) and the highest between first and second molar (3.56 mm). The thinnest and thickest buccal cortical thicknesses were detected on canine and first molar (1.04 mm) and on the second premolar and second molar (1.56 mm). Conclusion. The quantity and quality of the maxillary alveolar process is an important factor to decide where to insert the orthodontic miniscrews, necessitating careful preoperative evaluation.